2010
DOI: 10.4161/gmic.1.6.14076
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cell defensins and the regulation of the microbiome

Abstract: r ecently, our laboratory demonstrated that paneth cell defensins, innate antimicrobial peptides that contribute to mucosal host defense, are able to regulate the composition of the intestinal bacterial microbiome. using complementary mouse models of defensin deficiency (mmp7 -/-) and surplus (hd5 +/+ ), we noted defensin-dependent reciprocal shifts in the dominant bacterial species of the small intestine, without changes in total bacterial numbers. in addition, mice that expressed hd5 showed a significant los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 50 publications
(49 reference statements)
4
89
0
Order By: Relevance
“…It is likely that the nucleotide triphosphates represent just one factor in the overall regulation of the commensal bacterial population within the gut, working in concert with other endogenous factors, e.g., antibacterial peptides (29,49). The idea that extracellular nucleotide triphosphates inhibit bacterial growth in the intestine raises the question of whether these molecules play a similar role in other sites, e.g., the mouth, vagina, and urinary and respiratory tracts.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the nucleotide triphosphates represent just one factor in the overall regulation of the commensal bacterial population within the gut, working in concert with other endogenous factors, e.g., antibacterial peptides (29,49). The idea that extracellular nucleotide triphosphates inhibit bacterial growth in the intestine raises the question of whether these molecules play a similar role in other sites, e.g., the mouth, vagina, and urinary and respiratory tracts.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides are secreted into the gut lumen by leukocytes and epithelial cells and regulate host microbial interaction and the composition of the commensal microbiota [74,85]. The expression of -defensins by Paneth cells is associated with NOD2 signaling [86] and decreased -defensin production was observed in CD patients with NOD2 mutations [87,88] although it has also been raised that reduced -defensin production is only the consequence, and not the cause of the inflammation [89].…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Furthermore, non-commensal bacteria were selectively targeted and killed by α-defensins, while commensal microbiota were preserved. Equally, several studies have observed that the composition of the intestinal microbiome is directly influenced by alterations in the expression of AMPs [88,89].…”
Section: Amps and Gvhdmentioning
confidence: 99%